The Relationship Between Motivation and Student Work Readiness at SMKN 1 Lubuk Sikaping - Ahmad, Stevanni Amelia; Ganefri, Ganefri; Mukhaiyar, Riki (Universitas Pendidikan Ganesha, 2020)
This study aims to determine the relationship of motivation towards work readiness of class XII students in SMKN 1 Lubuk Sikaping. This type of research is quantitative with correlational research methods. This research was conducted at SMKN 1 Lubuk Sikaping. The population in this study are all students of class XII SMKN 1 Lubuk Sikaping. The sampling technique used isproportional random sampling, Selected as the sample in this study amounted to 169 students. Based on the test data analysis showed that the normal data and linear. The results of testing at significance level α of 0.05 (95% confidence level) r xy values obtained at 0.338 with 0.1456 rtabel because rhitung> rtabel then the hypothesis is accepted. This means that there is a relationship between motivation towards work readiness class XII students in SMK 1 Lubuk Sikaping.Keywords: Motivation, Work Readiness, Relation